Propolis and its Dental Applications: A Technological Prospection - de Carvalho Furtado Jr, João H.; Rocha Valadas, Lídia Audrey; Mendonça, Keniesd Sampaio; de Oliveira Filho, Rosueti Diógenes; Gadelha, Leandro M. U.; de Mello Fiallos, Nicole; Neto, Edilson Martins Rodrigues; de Mello Fiallos, Ana Cristina; de França Fonteles, Marta Maria (Recent Patents on Biotechnology, 2018)
Background: Propolis is a resinous complex produced by Apis mellifera L. bees whose variety of pharmacological properties results from the complexity of its composition. In dentistry, propolis is used on the prevention of oral diseases such as dental caries and gingivitis. Prospective studies in intellectual property banks are important to increase market competitiveness and thus generate new products in the various research areas. In this way, investments in patents play an important role in the technological and economic development of a country. Objective: To evaluate patents with dental products containing propolis, on intellectual property banks. Method: The research was conducted in 10 banks of intellectual property, including since the first deposits up to 2016. Relevant information that describes the invention in the patent document were collected, processed and described. Results: The search performed in 62 patents using propolis in the dental topic. World Intellectual Property Organization (WIPO) has the largest number of filing patents (83.60%) and the National Institute of Industrial Property (INPI) in third place with 4 patents (6.55%). Built-in dental cream with propolis was the most patented product. The first patent date of 1998, followed by an increase in the number of deposits in the last 20 years. Most of the patents are A61K code (51) for medical, dental or hygienic purposes. Conclusion: This study has shown that propolis is a promising bioactive component in dental products, especially for use in Cariology and Periodontology. Although there has been a significant progress in applications of propolis, the field of dental products is still a growing area and it is important to encourage innovation and development of new products incorporating propolis based on knowledge of its composition and therapeutic properties.
Keywords: intellectual property